2014
DOI: 10.1039/c3ra47315e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound technology and molecular sieves improve the thermodynamically controlled esterification of butyric acid mediated by immobilized lipase from Rhizomucor miehei

Abstract: In this research, the effects of ultrasound stirring and the addition of molecular sieves on esterification reactions between butyric acid and several alcohols catalyzed by immobilized lipase from Rhizomucor miehei (Lipozyme RM-IM) were studied. Among the tested alcohols, 1-propanol and isobutanol allowed the highest activities, whereas Lipozyme RM-IM showed poor activities for esterification using secondary and tertiary alcohols. Different solvents were also tested and n-hexane was selected because of its rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 38 publications
(53 reference statements)
2
44
0
Order By: Relevance
“…The test showed that the enzyme was stable in isoamyl alcohol confirming the fact that Novozym 435 was inhibited and not denatured at higher concentrations of isoamyl alcohol. In this study use of molecular sieves assisted in preventing accretion of water, hence averting hydrolysis and giving higher initial rates . Also, it has been observed that molecular sieves not only adsorb water formed in situ but also a small amount of acid as well .…”
Section: Kinetic Modellingmentioning
confidence: 84%
See 3 more Smart Citations
“…The test showed that the enzyme was stable in isoamyl alcohol confirming the fact that Novozym 435 was inhibited and not denatured at higher concentrations of isoamyl alcohol. In this study use of molecular sieves assisted in preventing accretion of water, hence averting hydrolysis and giving higher initial rates . Also, it has been observed that molecular sieves not only adsorb water formed in situ but also a small amount of acid as well .…”
Section: Kinetic Modellingmentioning
confidence: 84%
“…Kinetic energy of molecules rises with temperature and provides numerous collisions with the enzyme to enhance the rate of reaction . At higher temperatures, most of the interactions driving esterification and equilibrium processes, like miscibility, partitioning of substrates between the micro‐interface of enzyme–water, dissociation of acid as well as binding of substrate and interactions, are intensified . Moreover, the diffusion of components also increases at higher temperature due to the reduction in viscosity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipases (EC 3.1.1.3) are an important group of biocatalysts used in many biotechnological applications, such as in the synthesis of biopolymers, biodiesel, biolubricants, pharmaceuticals, agrochemicals, compounds used in the cosmetics industry, among others . These enzymes are able to catalyze distinct reactions, such as hydrolysis, esterification and transesterification, presenting enormous versatility in different types of organic synthesis, exhibiting high specificity and selectivity . In esterification reactions, for example, depending on the alcohol or carboxylic acid chain length, ester molecules exhibiting distinct properties are produced and can be employed for different purposes, such as emulsifiers, lubricants, flavor or cosmetic compounds …”
Section: Introductionmentioning
confidence: 99%